Outcomes of women treated with chemotherapy for ovarian cancer at CMJAH - Molebatsi, Justin Boitumelo I (My University, 2017)
Background Ovarian cancer remains an important cause of mortality in women worldwide. It is the leading cause of death from gynaecological cancers. Worldwide, it is diagnosed in more than 200 000 women annually and is responsible for over 125 000 deaths. In Southern Africa, it is estimated to contribute 3.3% of the total cancer mortality figures in women. The aim of this study was to review the 2 year recurrence free survival for women treated with chemotherapy for ovarian cancer in a South African tertiary care hospital. Methods This was a retrospective cohort of women with primary ovarian cancer treated with chemotherapy at the Charlotte Maxeke Johannesburg academic hospital between 2010 and 2014. Data were extracted from patient records using a standardized data extraction tool. Data was analysed using the STATA Software (StataCorp LP, USA). Precision was managed by using 95% confidence intervals. Results This study showed a 33.78% overall recurrence-free survival at 2 years. The association between surgical stage at presentation with recurrence status at 2 years showed no statistical significance (Pearson chi2(18) = 26.6848 P = 0.085). The difference in outcomes between patients treated with adjuvant chemotherapy and neo-adjuvant chemotherapy did not reach statistical significance (Pr = 0.157) Conclusion Despite extensive surgery and platinum based chemotherapy, this study demonstrates that prognosis for patients with advanced ovarian cancer remains poor with only a third of patients surviving recurrence-free at 2 years follow up
A research report submitted to the University of the Witwatersrand in fulfillment of the Master of Medicine Degree, Faculty of Health Sciences, 2017
Keywords: Chemotherapy; Cancer--Treatment--Complications